Icariin promotes functional recovery in rats after spinal cord injury by inhibiting YAP and regulating PPM1B ubiquitination to inhibiting the activation of reactive astrocytes - Feng, Sa; Liu, Linyan; Cheng, Yuelin; Zhou, Mengmeng; Zhu, Haoqiang; Zhao, Xinyan; Chen, Ziyu; Kan, Shunli; Fu, Xuanhao; Hu, Wei; Zhu, Rusen (Frontiers in Pharmacology, 2024)
The limited ability to regenerate axons after spinal cord injury (SCI) is influenced by factors such as astrocyte activation, reactive proliferation, and glial scar formation. The TGF-β/Smad (transforming growth factor-β/mothers against decapentaplegic homolog) pathway, associated with astrocytic scarring, plays a crucial role in recovery post-injury. This study aims to investigate how icariin (ICA) inhibits reactive astrocytes in spinal cord injury treatment. The research demonstrates that ICA can inhibit reactive astrocyte proliferation in rat post-injury by targeting YAP (Yes-Associated Protein). Furthermore, ICA enhanced functional recovery in female Wistar rats with spinal cord contusion, as evidenced by CatWalk XT gait analysis, BBB (Basso, Beattie, and Bresnahan) scores, and electrophysiological measurements. Knocking down PPM1B (protein phosphatase, Mg2+/Mn2+-dependent 1B) in astrocytes inhibits TGFβ signaling. Additionally, YAP was shown to regulate PPM1B ubiquitination and nuclear translocation through IP-WB (immunoprecipitation-Western Blot) ubiquitination and cytoplasm-nuclear separation. These findings contribute to our understanding of how ICA aids in spinal cord injury repair and offer insights for potential clinical applications.